Acupressure in the Management of Hyperemesis Gravidarum: A Systematic Analysis - Ariani, Novida (Sean Institute, 2024)
Pregnant women who experience more severe emesis gravidarum (nausea and vomiting) are known as hyperemesis gravidarum, this can affect the health of the mother and baby if not treated. To analyze and compile the latest scientific evidence to evaluate the benefits and techniques of acupressure as a method of managing emesis gravidarum, so that it does not develop into hyperemesis gravidarum. This research method is a systematic review with a systematic review based on PRISMA. Literature search based on research articles published in the last 10 years. Literature was obtained from a database of medium to high quality criteria using relevant keywords, namely